2020
DOI: 10.1177/1464993419886230
|View full text |Cite
|
Sign up to set email alerts
|

Does Microfinance Improve the Household Welfare of Ethnic Minorities? Evidence from Bac Kan Province, Vietnam

Abstract: Although a large number of studies have investigated the impacts of microfinance on rural households, their effects on ethnic minorities, who are among the left-behind groups, have not been evaluated. This study examines whether microfinancing provided by the Vietnam Bank for Social Policies (VBSP) improves the household welfare of ethnic minorities living in northern mountainous regions of Vietnam. A stratified random sampling technique is applied to a sample of 289 households. Propensity score matching (PSM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The overall family well-being with respect to better income, savings and expenditure are estimated in CSG households. Similarly, a study in Vietnam reported positive and consistent impacts of microfinance loans on total expenditure and educational expenditure, which supports the welfare effects of microfinance loans on ethnic minorities [ 41 ].…”
Section: Discussionmentioning
confidence: 62%
“…The overall family well-being with respect to better income, savings and expenditure are estimated in CSG households. Similarly, a study in Vietnam reported positive and consistent impacts of microfinance loans on total expenditure and educational expenditure, which supports the welfare effects of microfinance loans on ethnic minorities [ 41 ].…”
Section: Discussionmentioning
confidence: 62%
“…Khanam et al (2018) found that microfinance could help families/households cover their health care and/or education expenditure. Thu and Goto (2020) found that microfinance could help cover expenditure on education in ethnic minority households in Bac Kan province in Vietnam. Similarly, Viswanath (2018) conducted a study in India and found that microloans could help the members cover education expenses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The field of development economics is a highly interdisciplinary field. The dendrogram in (Few andTran, 2010, Nguyen, 2014) Poverty 142 (Nguyen et al, 2015, Cuong, 2011 Welfare 129 (Tran et al, 2018a, Coxhead et al, 2012 Institution 121 Pfau, 2009, Meschi et al, 2016) Inequality 96 Simkin, 2017, Walder andNguyen, 2008) Human Resource 77 (Mont andCuong, 2011, Tran et al, 2018b) Sustainability/Environment 75 (Christensen andBach, 2015, Nguyen et al, 2017b) FDI 70 (Le, 2017, Anwar and Economic Growth 62 (Nguyen et al, 2017a, Nguyen and Finance 61 (Dinh et al, 2019, Thu andGoto, 2020) Export/Import 59 (Hoang et al, 2020, Pham et al, 2019a Labor Productivity 57 (Huy andNonneman, 2016, Tung, 2017) Natural Resources 50 (Giesecke et al, 2013, Dinh et al, 2017 Trade Liberalization 47 (De Silva andPhuong, 2011, Kikuchi et al, 2018) Entrepreneurship 45 Nordman, 2018, Van Thang andFreeman, 2009) Migration 38 (Cuong andLinh, 2018, Hoang et al, 2012) Technology Development 29 Pomfret, 2011, Vuong andNancy, 2014) Unemployment 24 (Ho Dinh et al, 2020, Nguyen Hien Thu et al, 2020 Culture 12 (Nguyen et al, 2020b Urbanization 9 Nguyen Le, 2018, Arouri et al, 2017) Corruption 6 (Anh et al, 2016…”
Section: Research Topicsmentioning
confidence: 99%